Characteristics influencing location of death for children with life-limiting illness. Issue 6 (18th April 2013) - Chang, Emily; MacLeod, Rod; Drake, Ross
Abstract : Objective: To determine whether demographic and diagnostic characteristics were associated with location of death in a series of children with life-limiting illnesses. Design: A population-level case series was carried out by reviewing mortality records. Sociodemographic characteristics, diagnosis and referral to paediatric palliative care (PPC) were analysed for association with location of death. Setting: New Zealand Participants: Children and young people aged 28 days–18 years who died from a life-limiting illness between 2006 and 2009 inclusive. Main outcome measures: Location of death—home, hospital, other. Results: Of 494 deaths, 53.6% (256/494) died in hospital and 41.9% (203/494) died at home. Asian (OR=2.66, 95% CI 1.17 to 6.04) and Pacific children (OR=2.22, 95% CI 1.15 to 4.29) had an increased risk of death in hospital compared with European children, while children with cancer (adjusted OR=0.48, 95% CI 0.3 to 0.75) and children referred to the PPC service (adjusted OR=0.60, 95% CI 0.38 to 0.96) had a decreased risk. Population-attributable risk for referral to the PPC service was 28.2% (95% CI 11.25 to 47.75). Conclusions: Most children in New Zealand with a life-limiting illness die in hospital with a significant influence resulting from ethnic background, diagnosis and referral to the PPC service. These findings have implications for resourcing PPC services and end-of-life care.